An Improved Numerical Model of Shield Tunnel with Double Lining and Its Applications - Qi-xiang Yan; Chao-fan Yao; Wen-bo Yang; Chuan He; Ping Geng (Advances in Materials Science and Engineering)
Based on the existing numerical models of shield tunnel with double lining, an improved numerical model is developed and its rationality is verified by a similar model test. In the improved numerical model, lining, joint, and junction surface, respectively, are simulated by beam, spring, and a combination of compression bar and spring. Through the comparison of the numerical analysis results of the improved model and existing models, it turns out that the defects or problems in the existing numerical models are resolved; tension appearance on the contact surface and junction surface and the abrupt change of bending moment in linings are solved in the improved model because the compression bar element and the coupling technology of node displacement in the junction surface is applied. Therefore, the improved numerical model could be applied to analyze double lining with waterproof on the junction surface and separation of the junction surface under an unfavorable load. In this paper, the parameter formulas of element stiffness, applicable to the junction surface and contact surface of double lining, are given definitely, and the influence of the element amount of junction surface on the analysis results is discussed. Based on the improved numerical model, the mechanical behavior of the double lining of the Huangpu River Tunnel in China is studied, and some conclusions are obtained as follows. (1) The thickness increase of the double lining will clearly increase its bending moment, but it has little influence on its axial force. (2) The allocation proportion of the bending moment between the segment lining and secondary lining has no linear relationship with the ratio of the lining thickness.